European League Against Rheumatism (EULAR) Scleroderma Trial and Research group (EUSTAR) recommendations for the treatment of systemic sclerosis: methods of elaboration and results of systematic literature research. Issue 5 (28th October 2008) - Avouac, J; Kowal-Bielecka, O; Landewe, R; Chwiesko, S; Miniati, I; Czirjak, L; Clements, P; Denton, C; Farge, D; Fligelstone, K; Földvari, I; Furst, D E; et al.
Abstract : Objective: To describe methods and procedures used for the development of the European League Against Rheumatism (EULAR)/EULAR Scleroderma Trial and Research group (EUSTAR) recommendations for the treatment of systemic sclerosis. In particular, the results of a web-based Delphi exercise aimed at selection of research questions and evidence from systematic literature research, as parts of the development of these recommendations, are presented in detail. Methods: In agreement with the EULAR standard operating procedures a Task Force was created that consisted of the EUSTAR board members, 10 systemic sclerosis (SSc) experts invited from outside the EUSTAR board and representing Europe, the USA and Japan, a clinical epidemiologist, 2 patients with SSc and 3 fellows for literature research. All EUSTAR centres were invited to contribute to the development of recommendations through submission and preliminary selection of the research questions. The systematic literature research was performed using the Pubmed, Medline, EMBASE and Cochrane databases. Retrieved trials were evaluated according to the Jadad classification, and the level of evidence was graded from 1 to 4. Outcome data for efficacy and adverse events were abstracted and effect size, number needed to treat (NNT) and number needed to harm (NNH) were calculated when appropriate. Results: In all, 65 EUSTAR Centres provided 304 research questions concerning SSc treatment. These questions were aggregated, subdivided into 19 treatment categories and then subjected to preliminary selection by a web-based Delphi technique. The final set of 26 research questions was created by the Expert Committee based on the results of the Delphi exercise and the expert's experience. Conclusions: This paper is a comprehensive summary of the methods we used to build recommendations for the drug treatment of systemic sclerosis, combining an evidence based approach and expert opinion.